Should a single blastocyst transfer policy be a clinical decision or should it depend on the embryological evaluation on day 3? - Verheyen Greta; Camus Michel; Van den Abbeel Etienne; Van Landuyt Lisbet; Stoop Dominic; Devroey Paul (BMC, 2011)
Abstract Background Single blastocyst transfer has the advantage of maximizing the fresh single pregnancy rate. However, in patients with a low number of good quality embryos on day 3, it remains unclear whether immediate embryo transfer or further embryo culture with blastocyst transfer is the most preferable option. Methods A retrospective cohort study was carried out in which the outcome of 590 fresh in vitro fertilization (IVF) cycles over a 15 months period and their cryo cycles were analyzed. A total of 341 patients cycles had an elective day 5 strategy independent of intermediate embryo evaluation while another 249 patients underwent a day 5 embryo transfer only if at least four embryos were available on day 3. Blastocyst vitrification was performed using a closed high security system. Results Demographics, stimulation parameters and embryological data were comparable in the two groups. Patients in the elective day 5 group had a lower fresh transfer rate (90.62% vs. 95.18%, p < 0.05) as compared to patients with a day 3 or day 5 embryo transfer policy. No difference was observed in the fresh live birth rate and multiple pregnancy rate per initiated cycle (32.84% vs. 28.92%; 1.17% vs 0%) The projected cumulative ongoing pregnancy rate compensating for double counting in case subjects have more than one pregnancy is not different (42.58% vs. 39.84%). Conclusions Despite lower fresh transfer rates, elective single blastocyst transfer yields a similar projected cumulative ongoing pregnancy rate as in a policy with cleavage stage or blastocyst transfer depending on a good quality embryo count on day 3.